The effectiveness of petanque games in developing motor coordination in fifth-grade elementary school students - Muzakki, Abdurrohman; Arifin, Bustanol; Yoga, Heru Wardana; Aryanto, Sherif Juniar (Universitas Negeri Surabaya, 2026)
This study aims to examine the effectiveness of petanque games in improving motor coordination among fifth-grade elementary school students, particularly hand–eye and hand–foot coordination. A quasi-experimental design (nonequivalent control group design) was employed, involving 60 students selected through purposive sampling. The experimental group participated in Physical Education (PJOK) integrated with petanque games, while the control group received conventional instruction. Data were collected through coordination tests administered at pre-test and post-test stages and analyzed using paired sample t-tests and independent sample t-tests (α = 0.05). The results indicated that both groups had comparable baseline abilities (p > 0.05). After the intervention, the experimental group showed substantially greater improvements in hand–eye coordination (75.8 to 85.8; 21.60% increase) and hand–foot coordination (73.4 to 83.4; 21.30% increase) compared to the control group (7.10% and 8.20%, respectively). These findings demonstrate a strong practical effect of petanque-based learning on students’ motor coordination. In conclusion, petanque games are effective as a precision-based instructional strategy in physical education to enhance students’ coordination skills. Future research is recommended to employ more rigorous experimental designs and include additional variables such as balance and concentration.